Two rare case reports of confirmed Ceylon krait (Bungarus ceylonicus) envenoming in Sri Lanka. (1st March 2017) - Namal Rathnayaka, R.M.M.K.; Kularatne, S.A.M.; Kumarasinghe, K.D.M.; Jeganadan, K.; Ranathunga, P.E.A.N.
Abstract: The Ceylon krait ( Bungarus ceylonicus ) is a deadly venomous elapid snake endemic to Sri Lanka. Its habitat is mainly in the wet zone of the island. Despite its frequent encounters in and near human dwellings, reports of envenoming are rare and limited to four in the literature. The first and last fatal reports envenoming by B. ceylonicus was in 1993. After over two decades, we report two confirmed cases of B. ceylonicus bites-one a dry bite and the other with signs and symptoms of moderate envenoming. The envenoming occurred at night while the victim was asleep, causing tightness in the chest and dyspnoea on waking up, followed by neuromuscular paralysis that did not cause respiratory failure and complete recovery was observed three days following the bite. Highlights: Two cases of Ceylon krait ( Bungarus ceylonicus ) bites are described. One case is a dry bite and the other is a typical envenoming. Patients' history, examination, investigations and management are noted. A report after three decades regarding Bungarus ceylonicus bites in Sri Lanka.